2019
DOI: 10.1002/cam4.2529
|View full text |Cite
|
Sign up to set email alerts
|

ToxNav germline genetic testing and PROMinet digital mobile application toxicity monitoring: Results of a prospective single‐center clinical utility study—PRECISE study

Abstract: IntroductionIn this study (PRECISE), we assess the clinical utility of a germline DNA sequencing‐based test (ToxNav) for mutations in DPYD and ENOSF1 genes to alter clinician‐prescribed fluoropyrimidine doses and the use of a digital application (PROMinet) to record patient‐reported chemotherapy toxicity.Materials and methodsAdult patients with a histological diagnosis of colorectal cancer (CRC) who consented to fluoropyrimidine‐based chemotherapy were recruited prospectively and given a digital application to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In many countries there is still a lack of recommended systematic testing. Routine testing for the four variants with high level evidence highlighted by CPIC and DPWG is now recommended in the UK and the PRECISE study [ 22 ] demonstrated that a test including 3 of these variants as part of a larger panel (no marker for HapB3 included) provided clinically relevant information to clinicians prior to their prescribing chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In many countries there is still a lack of recommended systematic testing. Routine testing for the four variants with high level evidence highlighted by CPIC and DPWG is now recommended in the UK and the PRECISE study [ 22 ] demonstrated that a test including 3 of these variants as part of a larger panel (no marker for HapB3 included) provided clinically relevant information to clinicians prior to their prescribing chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used the extended ToxNav® (Oxford Cancer Biomarkers) panel that included three of the four CPIC alleles as the PRECISE study had shown that the rs56038477/rs75017182 HAPB3 allele indicated 75% enzyme activity and normal dose of 5-FU/Capecitabine was recomended [ 18 ] (more details are provided in Appendix B). In addition, ToxNav® included 15 more variants associated with DPYD function and one allele of the ENOSF1 gene [ 11 ].…”
Section: Methodsmentioning
confidence: 99%